ANALISIS BIAYA DIFERENSIAL DAN OPPORTUNITY COST DALAM PENGAMBILAN KEPUTUSAN MENJUAL ATAU MEMPROSES LEBIH LANJUT PADA PT. FORTUNA INTI ALAM - Pessak, Gabriel V.; Alexander, Stanly W.; Pusung, Rudy J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Companies need to make the right decisions in irder to achieve company goals. Decision making is certainly not an easy thing, because decision making will affect the performance of the company. Differential Cost and also opportunity cost are alternatives that companies can uses to make decisions where this analysis is used to obtain information on how much profit will be obtained if making decisions among the available alternatives. The purpose of this study is that management can make the right decisions between selling directly or processing it further using quantitative descriptive methods. The result obtained from the analysis using differential cost and also opportunity cost are better if PT. Fortuna Inti Alam further processes coffee beans into ground coffee. Because ground coffee has a higher selling price and PT. Fortuna Inti Alam will get a bigger profit.